2022
DOI: 10.1186/s40854-022-00335-8
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic or panic? A firm-level study on the psychological and industrial impacts of COVID-19 on the Chinese stock market

Abstract: This study presents a thorough investigation of the relationship between the coronavirus disease 2019 (COVID-19) and daily stock price changes. We use several types of COVID-19 patients as indicators for exploring whether stock prices are significantly affected by COVID-19’s impact. In addition, using the Chinese stock market as an example, we are particularly interested in the psychological and industrial impacts of COVID-19 on the financial market. This study makes two contributions to the literature. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…Further, there is some evidence that it decreased market informational efficiency, especially in the US and the UK (Ozkan 2021 ; Junior et al 2021 ). More importantly, using data from the Chinese stock market, Wang and Liu ( 2022 ) show that the shocks from the COVID-19 pandemic to the market was heterogeneous across industries, and the panic caused by the pandemic expanded volatility in daily returns. However, they note that the impulse of the shock from the pandemic tended to fade over time.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is some evidence that it decreased market informational efficiency, especially in the US and the UK (Ozkan 2021 ; Junior et al 2021 ). More importantly, using data from the Chinese stock market, Wang and Liu ( 2022 ) show that the shocks from the COVID-19 pandemic to the market was heterogeneous across industries, and the panic caused by the pandemic expanded volatility in daily returns. However, they note that the impulse of the shock from the pandemic tended to fade over time.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we can conduct more in-depth research and analysis with spatial econometric models. Now facing the shocks of COVID-19 (Wang and Liu 2022 ; Liu et al 2022 ), the development of the housing market in China become more diverse. Therefore, the method and basic results shown in this study are still useful in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…On short-selling, irrational investors will tend to make transactions, while their pessimistic investors buy stocks that fall in the hope of higher returns after the pandemic. The results of a study conducted by Wang & Liu [ 36 ] on the Chinese stock market showed that the COVID-19 pandemic caused panic in the stock market, which suppressed stock prices and increased volatility in daily returns.…”
Section: Literature Reviewmentioning
confidence: 99%